Mirazón Lahr et al. reply - Lahr, M.; Rivera, F.; Power, R.K.; Mounier, A.; Copsey, B.; Crivellaro, F.; Edung, J.E.; Fernandez, J.M.; Kiarie, C.; Lawrence, J.; Leakey, A.; Mbua, E.; et al. (Nature Publishing Group, 2016)
Replying to C. M. Stojanowski et al. Nature 539, 10.1038/nature19778 (2016) "Contesting the massacre at Nataruk".